Effects of low levels of herbicides on prairie species of the Willamette Valley, Oregon. (16th September 2013) - Olszyk, David; Blakeley‐Smith, Matthew; Pfleeger, Thomas; Lee, E. Henry; Plocher, Milton
Abstract The relative sensitivity of 17 noncrop plant species from Oregon's Willamette Valley was determined in response to glyphosate, tribenuron methyl (tribenuron), and fluazifop‐p‐butyl (fluazifop) herbicides. For glyphosate, Elymus trachycaulus, Festuca arundinacea, Madia elegans, Potentilla gracilis, and Ranunculus occidentalis were the most sensitive species, based on a concentration calculated to reduce shoot dry weight by 25% (IC25 values) of 0.02 to 0.04 × a field application rate of 1112 g active ingredient (a.i.) per hectare. Clarkia amoena and Lupinus albicaulis were the most tolerant to glyphosate, with IC25 values near the field application rate. Clarkia amoena, Prunella vulgaris, and R. occidentalis were the most sensitive to tribenuron, with IC25 values of 0.001 to 0.004 × a field application rate of 8.7 g a.i. ha−1 for shoot dry weight. Five grass species were tolerant to tribenuron with no significant IC25 values. For fluazifop, 2 native grasses, E. trachycaulus and Danthonia californica, were the most sensitive species, with IC25 values of 0.007 and 0.010 × a field application rate of 210 g a.i. ha−1, respectively, for shoot dry weight, while a native grass, Festuca roemeri, and nearly all forbs showed little or no response. These results also indicated that the 3 introduced species used in the present study may be controlled with 1 of the tested herbicides: glyphosate (F. arundinacea), tribenuron (Leucanthemum vulgare), and fluazifop (Cynosurus echinatus). Environ Toxicol Chem 2013;32:2542–2551. © 2013 SETAC